Semiotika Arsitektur Tradisional Sumbawa - Amiuza, Chairil Budiarto (RUAS, 2017)
The architecture of traditional houses in Sumbawa Regency still has a correlation between the layout design, the purpose-use and the meanings with the society, environment, and its unique culture, both in the upper and lower social strata. Local identity in an architecture that grows in society has a hidden meaning both visually and non-visually. As artifacts that are quite complex in describing the culture of a community group, traditional architecture comes with explicit or implicit messages. Therefore, it needs a syntactic, pragmatic and semantic approach in reading the message. A qualitative approach is used to explore architectural objects in the study area based on the views of the local community and their meanings also follow the local understanding path that develops around the study area. The visual representation and visual representation of the built-up elements revealed the hidden meaning of the sign. The application of strata and codification of visual traits can reflect the growing cultural values in society about the harmony between man and nature through his built environment.